Clinical outcome of Two Minute Walk Test after return to run program in IDEO users: a retrospective study - Lockwood, Michelle D.; Hovorka, Christopher F.; Baumann, Molly E.; Childers, W. Lee (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveTo investigate clinical improvement in persons with severe musculoskeletal injuries following a 4-week high intensity sports-based return to run rehabilitation therapy program (RTR) combined with use of an Intrepid Dynamic Exoskeletal Orthosis (IDEO).Patients41 persons (37 male and 4 female) with lower limb musculoskeletal injuries undergoing treatment and rehabilitation at the Center for the Intrepid were included in the retrospective cohort study.MethodsRetrospective analysis of clinical data was used to identify changes in Two Minute Walk Test (2MWT) outcomes in patients with lower limb musculoskeletal injuries without the IDEO, with the IDEO alone and after IDEO + RTR. A repeated measures ANOVA was used to examine differences in distance walked across the three groups (NO IDEO, IDEO alone, and IDEO + RTR). Bonferroni post-hoc analysis was performed, and a level of significance was set at 0.05.ResultsA statistically significant difference in distance walked between all groups was observed (p < 0.001). Patients' mean distance walked using the IDEO alone (179 m, p < 0.001) and IDEO + RTR (208 m, p < 0.001) increased significantly compared to NO IDEO (152 m, p < 0.001). These differences surpass the Minimal Clinically Important Difference (37.2 m) and the Minimal Detectable Change (34.3 m) for the 2MWT in the limb loss population.ConclusionThese data suggest the potential benefit of the combination of IDEO + RTR improved walking in patients with lower limb musculoskeletal injuries and suggest the 2MWT may be a meaningful, simple measure to detect improvement in function.